PENGETAHUAN ANAK SD MEMILIKI HUBUNGAN YANG BERMAKNA DENGAN CARA MEREKA MEMILIH MAKANAN JAJANAN - islam, fahrul; Lestari AR, Ayu; Ahmad, Haeranah (Jurnal Sanitasi Profesional Indonesia, 2025)
Children are at high risk of contracting disease through consumption of food and drink. According to information from the World Health Organization (WHO), it is estimated that around 2 million people die every year due to diseases caused by food, including children. The purpose of this study was to determine the relationship between elementary school children's knowledge and their actions in choosing snacks. The research method used is a cross-sectional method which is analytical observational in nature. This research was conducted using a purposive sampling technique. Data was collected using a knowledge questionnaire and an action questionnaire with a sample size of 102 respondents. Data analysis used chi-square. Results: As many as 68.6% of elementary school children's knowledge level about choosing snack foods was in the good category and 67.6% of elementary school children's actions in choosing snack foods were in the good category. The results of statistical test analysis show that the p value = 0.001 is smaller than 0.05. Conclusion: There is a significant relationship between elementary school students' level of knowledge and the way they choose snacks. Students are expected to be more careful when choosing snacks. The school is expected to provide additional knowledge and examples of positive behavior in choosing snacks and consider providing a healthy canteen. It is recommended that future researchers continue this research with a wider research location and a larger number of respondents.